Acute nociceptive stimuli rapidly induce the activity of serotonin and noradrenalin neurons in the brain stem of awake mice. (December 2019) - Moriya, Shunpei; Yamashita, Akira; Nishi, Ryusei; Ikoma, Yoko; Yamanaka, Akihiro; Kuwaki, Tomoyuki
Abstract: Nociception is an important type of perception that has major influence on daily human life. There are some descending pathways related to pain management and modulation, which are collectively known as the descending antinociceptive system (DAS). Noradrenalin (NA) in the locus coeruleus (LC) and serotonin (5-HT) in the rostral ventromedial medulla (RVM) are components of the DAS. Most 5-HT neurons in the dorsal raphe (DR) have ascending projections rather than descending projections, and they project to the thalamus that modulates nociception. Both the DAS and the DR are believed to be involved in pain-emotion symptoms. In this study, we utilized a fiber photometry system to specifically examine the activity of LC NA neurons and RVM/DR 5-HT neurons using mice carrying tetracycline-controlled transactivator transgene (tTA) under the control of either a dopamine β-hydroxylase promoter or a tryptophan hydroxylase-2 promoter and site-specific infection of an adeno-associated virus carrying a TetO G-CaMP6 gene. After confirmation of specific expression of G-CaMP6 in the target populations, changes in green fluorescent signal intensity were recorded in awake mice upon exposure to acute nociceptive stimulation consisting of a pinch and application of heat (55 °C) to the tail. Both stimuli resulted in rapid and transient (<15 s) increases in the activity of LC NA neurons and RVM/DR 5-HT neurons while the control stimuli did not induce any changes. The present results clearly indicate that acute nociceptive stimuli increase the activity of LC NA neurons and RVM/DR 5 H T neurons and suggest a possible therapeutic target for pain treatment.